2017
DOI: 10.1088/1757-899x/209/1/012056
|View full text |Cite
|
Sign up to set email alerts
|

Development of Anticorrosive Polymer Nanocomposite Coating for Corrosion Protection in Marine Environment

Abstract: The marine environment is considered to be a highly aggressive environment for metal materials. Steels are the most common materials being used for shipbuilding. Corrosion is a major cause of structural deterioration in marine and offshore structures. Corrosion of carbon steel in marine environment becomes serious due to the highly corrosive nature of seawater with high salinity and microorganism. To protect metallic materials particularly steel against corrosion occurrence various organic and inorganic coatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…[27][28][29] NPs were observed to modify the surface energy of the inherently hydrophobic siloxane polymers and hence improve the performance of nanocomposite coating immersed in aggressive media. 30 There are a number of ways to improve the properties of nanocomposites by incorporating NPs, fibers, glass beads, etc. Reinforcements are found to improve thermal resistance, corrosion resistance and mechanical properties of metal matrix due to their unique properties.…”
Section: Nanocomposite Coatingmentioning
confidence: 99%
See 1 more Smart Citation
“…[27][28][29] NPs were observed to modify the surface energy of the inherently hydrophobic siloxane polymers and hence improve the performance of nanocomposite coating immersed in aggressive media. 30 There are a number of ways to improve the properties of nanocomposites by incorporating NPs, fibers, glass beads, etc. Reinforcements are found to improve thermal resistance, corrosion resistance and mechanical properties of metal matrix due to their unique properties.…”
Section: Nanocomposite Coatingmentioning
confidence: 99%
“…A wide range of epoxy resins are produced industrially for different technological applications. 39 Mardare et al 30,40 experimented with the effect of pristine and TiO 2 incorporated epoxy paint on the corrosion properties of naval steel plates immersed in sea water. A two component polyamide with glossy acrylic PU was coated at a thickness of $80 mm on steel.…”
Section: Enhancement In Corrosion Resistancementioning
confidence: 99%
“…Polymer nanocomposite coatings have been thoroughly investigated in which their applications span from imaging, anticorrosion, marine, smart packaging materials, automotive industry to high technology applications [ 145 , 146 , 147 ]. Nanocomposite coatings can provide high-efficiency gas barrier to the substrate foil [ 148 ] and they can provide superior anti-scratch and anti-corrosion properties.…”
Section: Click Chemistry-based Methodologies In Polymer Nanocomposmentioning
confidence: 99%
“…Mardare and Benea [117] evaluated the performance of anticorrosive polymer nanocomposites coatings in the marine environment. For this purpose, they selected naval steel for the experiments in sea water.…”
Section: Nanotechnology Applications In Transportation Vehiclesmentioning
confidence: 99%
“…Three steel surfaces named as E32 uncoated steel; E32 with primer (painting) and E32 with primer + TiO 2 nanoparticles were prepared to evaluate their performance against corrosion in seawater. From the results, it was found that the corrosion rate was very high in the case of E32 uncoated steel [117]. Contrarily, E32 with primer + TiO 2 nanoparticles surface layer showed a tremendously lower corrosion rate which indicated that nanoparticle coatings have higher corrosion resistance in seawater as shown in Figure 12.…”
Section: Nanotechnology Applications In Transportation Vehiclesmentioning
confidence: 99%